The economic integration of Europe - Pomfret, Richard W. T. (Harvard University Press, 2021)
"Richard Pomfret documents European integration since WWII, showing that today's European Union is the product less of master planning than of responses to political and economic challenges. Nevertheless, the EU emerges as a world-historic achievement in cross-border cooperation, with a bright but challenging future"--